The Impact of Disparity in Infrastructure Development on Aceh’s Economic Performance: An Inter-Provincial Analysis - Mutiara Fahmi; Sahara Sahara; Yeti Lis Purnamadewi (Institute for Economic and Social Research, 2020)
This study provides empirical findings on regional disparity in infrastructural facilities in 23 districts/municipalities of Aceh Province and the impact of the disparity on the economic performance of Aceh Province, specifically on those of economic growth, poverty, and unemployment. The unit of analysis is the district level and the Infrastructure Development Index (IDI) is used as the variable computed by using the multivariate method. Regional disparity is measured by the Coefficient of Variation and the impact of IDI on the province’s economy is analyzed using the econometric model. The analysis shows that infrastructure development disparity exists and that IDI generally affects the economic performance in Aceh Province. Specifically, the results reveal that electricity provision, the number of hotels, and the length of road positively correlate with economic performance. However, the number of Base Transceiver Stations, the number of markets, and the number of banks do not necessarily lead to higher economic performance. The policy implications of the findings are discussed.